Significance of Lean, Agile and Leagile Decoupling Point in Supply Chain Management - Faiza Amir (Journal of Economics and Behavioral Studies, 2011)
A supply chain is a system, consisting of material suppliers, production facilities, distribution services and customers. These are all linked together through the downstream feed forward flow of materials and the upstream feedback flow of information. Several organizations have adopted the concept of â€œLeanâ€ to improve the performance and position in the market place and. The â€œAgileâ€ manufacturing has been recently emerged as a customer demand driven option. It defines as using market knowledge and virtual corporation to exploit profitable opportunities in a volatile marketplace, leanness stands for developing a value stream to eliminate all waste, including time and to ensure a level schedule. Leagile is one suitable way to exploit the both approaches, lean and agile. It requires the selection and setting up of a material flow decoupling point. The positioning of the decoupling point, therefore, depends upon the longest lead-time and at the same time customer is prepared to tolerate this time lag and the point at which variability in product demand dominates. Downstream from the decoupling point all products are pulled by the customer demand, that is why that part of supply chain is market driven. Upstream from the decoupling point the supply chain is essentially forecast driven. This review paper will explore the approaches of lean, agile and leagile decoupling point to suggest the most suitable supply chain practices, processes and procedures. Several factors are needed for lean and agile practicesâ€™ success; not only is it necessary to implement most of the technical tools but an organizationâ€™s culture needs transforming too.